Post-Invasion Reflection in the Works of Budzhak Artists - Shevchuk, Tetyana (Journal of Danubian Studies and Research, 2023)
The 2022 war became a serious trigger for the artists of Budzhak and all of Ukraine to comprehend the tragic turning point in the life of the country associated with the attempt of the aggressor country to destroy the national identity of the Ukrainians. The article deals with the main concepts and symbols of the new post-invasion reality in the regional art (house, key, fire, well, prayer, holy patronage).